CIMPAL expanded: unraveling the cumulative impacts of invasive alien species, jellyfish blooms, and harmful algal blooms - Marina Chiappi; Marina Chiappi; Marina Chiappi; Yolanda Stranga; Chrysanthi Kalloniati; Konstantinos Tsirintanis; George Tsirtsis; Ernesto Azzurro; Ernesto Azzurro; Stelios Katsanevakis (Frontiers in Marine Science)
The introduction of invasive alien species (IAS) and the occurrence of jellyfish blooms and harmful algal blooms (HABs) can significantly alter native biodiversity and disrupt ecosystem functioning. This study expands the Cumulative IMPacts of invasive ALien species (CIMPAL) index to assess the cumulative impacts of IAS, HABs, and jellyfish blooms, also accounting for interspecific interactions. The approach is implemented in the Aegean Sea, analyzing data on 26 alien species (including one jellyfish), seven phytoplankton species responsible for HABs, and four native jellyfish species known to cause blooms. The application of CIMPAL revealed the spatial patterns and the relative importance of impacts across the Aegean Sea, identifying the most affected areas and ranking species based on four impact indicators. The results indicated that IAS contributed the most to cumulative impacts, with the highest scores observed in confined southern coastal areas of the Aegean Sea. Consequently, highly impacted coastal regions due to IAS were more prevalent in the southern Aegean compared to the north. In contrast, cumulative impacts in open waters decreased from the northern to the southern Aegean. HABs and jellyfish blooms also caused considerable impacts, particularly in certain gulfs. This study provides essential spatially explicit information to support effective management and mitigation of these environmental challenges in the Aegean Sea.